Occupational management in the workplace and impact on injury claims, duration, and cost: a prospective longitudinal cohort - Lemstra ME (Dove Medical Press, 2016)
Mark E Lemstra Alliance Health Medical Clinic, Moose Jaw, SK, Canada Abstract: Few workplaces have prospectively reviewed workplace and worker issues simultaneously and assessed their impact on Workers’ Compensation Board (WCB) claims. In January of 2014, each worker in a large workplace in Saskatchewan, Canada, was prospectively followed for 1 year to determine factors that impact injury claim incidence, recovery, and costs. In total, 207 out of 245 workers agreed to complete the baseline survey (84.5%). In 2014, 82.5% of workers had self-reported pain, but only 35.5% submitted a WCB claim. Binary logistic regression was used to compare those with pain who did not submit a WCB injury claim to those with pain who did initiate a WCB claim. Independent risk factors associated with WCB claim incidence included depressed mood (odds ratio [OR] =2.75, 95% confidence interval [CI] 1.44–9.78) and lower job satisfaction (OR =1.70, 95% CI 1.08–10.68). Higher disability duration was independently associated with higher depressed mood (OR =1.60, 95% CI 1.05–4.11) and poor recovery expectation (OR =1.31, 95% CI 1.01–5.78). Higher cost disability claims were independently associated with higher depressed mood (OR =1.51, 95% CI 1.07–6.87) and pain catastrophizing (OR =1.11, 95% CI 1.02–8.11). Self-reported pain, physically assessed injury severity, and measured ergonomic risk of workstation did not significantly predict injury claim incidence, duration, or costs. In January 2015, the workplace implemented a new occupational prevention and management program. The injury incidence rate ratio reduced by 58% from 2014 to 2015 (IRR =1.58, 95% CI =1.28–1.94). The ratio for disability duration reduced by 139% from 2014 to 2015 (RR =2.39, 95% CI =2.16–2.63). Costs reduced from $114,149.07 to $56,528.14 per year. In summary, WCB claims are complex. Recognizing that nonphysical factors, such as depressed mood, influence injury claim incidence, recovery, and costs, can be helpful to claims management. Keywords: workplace, Workers Compensation Board, injury claim, depressed mood, return-to-work program, job satisfaction